The Church at the Turning Points of History - Kurth, Godefroid (Norfolk, VA Gates of Vienna Books/IHS Press, 2007)
Having survived 2,000 years of attacks, emperors, kings, traditions and philosophies, and heresies and schisms, the Catholic church and its place in history are the focus of this chronicle. This miracle of constant regeneration, the book explains, is bo
Keywords: Church history